2005
DOI: 10.1038/sj.hdy.6800743
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation and covariation for resistance and tolerance to Cucumber mosaic virus in Mimulus guttatus (Phrymaceae): a test for costs and constraints

Abstract: Genetic variation for resistance and tolerance to pathogens may be maintained by costs represented as genetic tradeoffs between these traits and fitness. The evolution of resistance and tolerance also may be constrained by negative genetic correlations between these defense systems. Using a complete diallel, we measured genetic variation and covariation for and among performance, resistance, and tolerance traits in Mimulus guttatus challenged with a generalist pathogen, Cucumber mosaic virus (CMV). Viral coat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 34 publications
(45 citation statements)
references
References 69 publications
2
40
1
2
Order By: Relevance
“…Our results suggest that any fitness costs of tolerance and resistance are not equivalent in M. guttatus, which would limit the opportunity for tradeoffs to arise. Similarly, Carr et al (2006) found no evidence for tradeoffs between tolerance and resistance to Cucumber mosaic virus in M. guttatus. The potential costs that we examined were presumably associated with constraints on resource allocation to other functions, specifically growth or reproduction.…”
Section: Genetic Variation For Herbivory Defense In Mimulusmentioning
confidence: 89%
See 2 more Smart Citations
“…Our results suggest that any fitness costs of tolerance and resistance are not equivalent in M. guttatus, which would limit the opportunity for tradeoffs to arise. Similarly, Carr et al (2006) found no evidence for tradeoffs between tolerance and resistance to Cucumber mosaic virus in M. guttatus. The potential costs that we examined were presumably associated with constraints on resource allocation to other functions, specifically growth or reproduction.…”
Section: Genetic Variation For Herbivory Defense In Mimulusmentioning
confidence: 89%
“…These nonadditive sources of variation would have been impossible to observe without the diallel breeding design that we used; moreover, with a clonal or nested half-sib design, we would have overestimated the magnitude of heritability in our traits (Lynch and Walsh, 1998). Interestingly, another study involving a different population of M. guttatus also reported within-population nonadditive genetic variation for the same traits (Carr et al, 2006), which indicates that complex genetic effects for such traits may be more widespread than previously appreciated. In addition, there was some evidence for environment-dependent expression of nonadditive genetic variation; the presence of spittlebugs reduced the magnitude of nonadditive genetic variation in flower number (Table 2), which suggests that herbivory could dampen the influence of nonadditive genetic variation on natural selection for this trait.…”
Section: Genetic Variation For Herbivory Defense In Mimulusmentioning
confidence: 93%
See 1 more Smart Citation
“…[57,58]). However, a neutral or negative correlation does not conclusively eliminate the possibility of a cost.…”
Section: (D) Statistical Analysis (I) Testing For Genetic Variance Inmentioning
confidence: 99%
“…greater association with mutualist partners) also have lower relative fitness in the absence of the exploiter (cf. [57,58]). However, we found the opposite (albeit nonsignificant) trend, where lines with a low proportion of non-fixing nodules showed higher relative biomass in the mutualist treatment (r ¼ 20.12676, p ¼ 0.1890; figure 2), indicating that no cost to filtering exploitative rhizobia partners was detected despite a large quantitative genetic design (n ¼ 110 plant lines).…”
Section: (D) There Is No Cost To Excluding Exploitative Partnersmentioning
confidence: 99%